“The Argumentative Function of the Exemplary Metaphor in the Qur’anic Discourse: Surah Al-Isra’ as a Model.” - .cheikh, amal (El Omda in Linguistics and Discourse Analysis, 2026)
This research examines the argumentative function of representative metaphor in the Qur’anic discourse, with a particular focus on Surat Al-Isra’. It highlights its role in transforming abstract meanings into vivid, sensory images that persuade and influence the audience. The study reveals that representative metaphor contributes to clarifying Qur’anic concepts and deepening the argumentative dimension of the discourse, thereby enhancing its power to shape awareness and strengthen faith.